Determinasi Faktor Sosiodemografi, Diagnosis, dan Lama Perawatan terhadap Kualitas Hidup Caregiver Pasien dengan Gangguan Jiwa Berat - dbysinth, dbysinthania; Milya Novera; Mariza Elvira; Putri Minas Sari; Anggra Trisna Anjani (Jurnal Amanah Kesehatan, 2025)
Caregivers of patients with severe mental illness often experience physical and emotional burdens that impact their quality of life. This study aims to identify the sociodemographic factors that most significantly influence the quality of life of caregivers. This analytical study involved 114 caregivers selected through accidental sampling from a population of from a population of 2,189 individuals. Bivariate and multivariate linear regression analyses were conducted to evaluate the influence of various characteristics on caregivers' quality of life. Multivariate analysis results indicated that educational level (p = 0.046; B = 1.061) and age (p = 0.000; B = -0.514) had significant relationships with caregiver quality of life. The conclusion is that educational level is the dominant factor influencing caregiver quality of life. Education-based interventions can be an important strategy for improving their quality of life.